SEASONAL AND INTRA-SEASONAL VARIABILITY OF SEA SURFACE TEMPERATURE IN PARI ISLAND-JAKARTA, INDONESIA - Corry Corvianawatie (Jurnal Kelautan, 2019)
Sea Surface Temperatures (SSTs) is one of the most important oceanographic parameter that could affect the marine life, especially coastal ecosystem. SSTs data varies in hourly, daily, seasonal, annual, inter-annual, and even in longer time scales. This condition makes any studies using instantaneous measurement could turn into misleading report due to the lack of time series SSTs data. Thus, the aim of this study is to understand the seasonal and intra-seasonal SSTs dynamics in Pari Island using continuous measurement from temperature logger. This study found that the double peaks of SSTs in May and November are correspond to the period of transitional monsoon. Conversely, the two minimum SSTs in February and August were correspond to the peak of northwest monsoon and southeast monsoon respectively. In addition to seasonal pattern, the slightly dominant intra-seasonal variability of SSTs was found in the period of 57 and 86 days. Those predominant signals suggested represent the Madden-Julian Oscillation phenomena.